Statistical year book benue-plateau state 1974 - Plateau state of Nigeria (Jos, Nigeria : Ministry of economic planning statistics and demographic division, 1974)
The data are in respect of Benue-Plateau state of Nigeria with the exception of a few tables on population, agriculture and tin mining which cover the federation as a whole.
nmn, 23/04/19
Ref.
Keywords: Statistical report; Statistical year book; Benue - Plateau State